ANALISIS KEARIFAN LOKAL PADA PETANI KEMENYAN YANG RAMAH LINGKUNGAN DI DESA HUTAGURGUR KECAMATAN DOLOK SANGGUL KABUPATEN HUMBANG HASUNDUTAN PROVINSI SUMATERA UTARA - Yusni Kristiani; Eri Sayamar; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research was conducted  in Hutagurgur village, subdistrict Dolok Sanggul Humbang Hasundutan village. This study aims to analysed of local wisdom had been done or ever, also to know the interest level and strenght level of benzoin farmer base on local wisdom benzoin farming that eco friendly. The purpose from this research is to identify the local wisdom strenght that still continue in society living of Hutagurgur village, to know strenght that used on eco friendly benzoin farming. Method  that use is qualititatively where is the method that use to research in the condition of  natural object. Technical sampling in this study using snowball sampling technique in sequence until saturation point from  the questions is attained. With deeply interview method  to respondents and record it in the form of  voice record using questionnaire which had been made before. The local wisdom is a form of knowledge, beliefs, rules, customs, and habits conducted by a society that respects the norms and values of the culture that has been there earlier and  passed on children and nephew in the running of everyday life. In this study, there is local wisdom that still going, althought the procedures, traditional events even  rules is not running as before. Keywords: Local Wisdom,Environment, Strenght, StrategyLocal Wisdom